Diaconia e espiritualidade - Heise, Ekkehard (2013)
The text initially reflects on “diaconics”, understood as the science that studies the issue of diaconia. It describes some difficulties in the study of diaconia and then presents a Latin American contribution that can help to overcome them. The first part concludes with considerations about diaconics as a part of practical theology. The second part analyzes some major issues in the present discussion on diaconics. The third part is a reflection on the relationship between diaconia and spirituality, searching for a diaconic spirituality that can sustain Christian diaconia. Historical models of such a spirituality are then described, concluding with an analysis of the theme in Martin Luther’s theology.